Micronutrients May Be a Unique Weapon Against the Neurotoxic Triad of Excitotoxicity, Oxidative Stress and Neuroinflammation: A Perspective - Holton, Kathleen F. (Frontiers in Neuroscience, 2021)
Excitotoxicity has been implicated in many neurological disorders and is a leading cause of oxidative stress and neuroinflammation in the nervous system. Most of the research to date has focused on each of these conditions individually; however, excitotoxicity, oxidative stress, and neuroinflammation have the ability to influence one another in a self-sustaining manner, thus functioning as a “neurotoxic triad.” This perspective article re-introduces the concept of the neurotoxic triad and reviews how specific dietary micronutrients have been shown to protect against not only oxidative stress, but also excitotoxicity and neuroinflammation. Future dietary interventions for neurological disorders could focus on the effects on all three aspects of the neurotoxic triad.